Selective attention to question-relevant text information precedes high-quality summaries: Evidence from eye movements - José A. León; José David Moreno; Inmaculada Escudero; Johanna K. Kaakinen (Bern Open Publishing, 2019)
Comprehension and summarizing are closely related. As more strategic and selective processing during reading should be reflected in higher quality of summaries, the aim of this study was to use eye movement patterns to analyze how readers who produce good quality summaries process texts. 40 undergraduate students were instructed to read six expository texts in order to respond a causal question introduced in the end of the first paragraph. After reading, participants produced an oral summary of the text. Based on the quality of the summaries, participants were divided into three groups: High, Medium and Low Quality Summaries. The results revealed that readers who produced High Quality Summaries made significantly more and longer fixations and regressions in the question-relevant parts of texts when compared to the other two summary groups. These results suggest that the summary task performance could be a good predictor of the reading strategies utilized during reading.